Planning deficits in Huntington's disease: A brain structural correlation by voxel-based morphometry. - Jesus Calderon-Villalon; Gabriel Ramirez-Garcia; Juan Fernandez-Ruiz; Fernanda Sangri-Gil; Aurelio Campos-Romo; Victor Galvez (PLoS ONE, 2021)
Introduction Early Huntington's disease (HD) patients begin to show planning deficits even before motor alterations start to manifest. Generally, planning ability is associated with the functioning of anterior brain areas such as the medial prefrontal cortex. However, early HD neuropathology involves significant atrophy in the occipital and parietal cortex, suggesting that more posterior regions could also be involved in these planning deficits. Objective To identify brain regions associated with planning deficits in HD patients at an early clinical stage. Materials and methods Twenty-two HD-subjects genetically confirmed with incipient clinical manifestation and twenty healthy subjects were recruited. All participants underwent MRI T1 image acquisition as well as testing in the Stockings of Cambridge (SOC) task to measure planning ability. First, group comparison of SOC measures were performed. Then, correlation voxel-based morphometry analyses were done between gray matter degeneration and SOC performance in the HD group. Results Accuracy and efficiency planning scores correlated with gray matter density in right lingual gyrus, middle temporal gyrus, anterior cingulate gyrus, and paracingulate gyrus. Conclusions Our results suggest that planning deficits exhibited by early HD-subjects are related to occipital and temporal cortical degeneration in addition to the frontal areas deterioration.